Ecobrick: Inovasi Cerdas Ciptakan Lingkungan Hijau Melalui Pengelolaan Sampah Plastik - Pani Satwikanitya; Devi Shofia Ayu Amalia; Aida Nur Mashito Putri; Ahmad Musonnifin Aziz; Yulia Tri Rahkadima; Listin Fitrianah; Mohamad Ikhwanuddin; Andi Nur Zainuri; Dona Asah Rohmadi; Yuli Winarto; Medya Ayunda Fitri; Trisna Kumala Dhaniswara; Zahrotul Azizah; Aris Kuswanto (Journal of Science and Social Development, 2026)
Plastic waste is a growing environmental problem in Indonesia and negatively impacts environmental sustainability. This activity aims to raise public awareness about plastic waste management through the ecobrick method. The activity was carried out online through a National Webinar organized by the Chemical Engineering Study Program, Nahdlatul Ulama University, Sidoarjo. The webinar implementation consisted of preparation, implementation, and reporting stages. The material presented discussed the impact of plastic waste and the stages of ecobrick making, from the process of cleaning, drying, cutting, compacting, and assembling plastic waste into useful products. The results of the activity showed that participants gained a new understanding and awareness of the importance of wise plastic waste management. Participants also understood the benefits of ecobricks as an alternative environmentally friendly product that can be used as a simple construction material and decorative element. Thus, this activity is expected to encourage public participation in creating a cleaner and greener environment through sustainable plastic waste management.